Scientific rationality and perceived effectiveness of indigenous technical knowledge on coconut (Cocos nucifera L.) cultivation in Kerala - Husain, A. Sakeer; Sundaramari, M. (Journal of Tropical Agriculture, 2011)
We documented 129 traditional practices (indigenous technical knowledge, ITK) on coconut cultivation in Kerala. Aspects such as collection and storage of seed nuts (20.15%), cultural operations (14.73%), manuring (13.95%) and nursery management (13.18%) constituted the dominant categories of indigenous knowledge. Of the 129 practices, 30 were analyzed for their scientific rationality and awareness and adoption among farmers and 19 practices studied for their perceived effectiveness. Of the 30 practices, 24 were found to be rational, while the rest six were adjudged as irrational. The scientific rationale/operational principles behind 24 rational ITK were also elucidated in this study. Farmers’ knowledge on a majority of selected ITK was good with more than 50% of the sampled farmers (52.50 to 92.50% per practice) having awareness on 20 practices. Twelve practices were adopted by 57.5 to 82.5% farmers. Of the 19 ITK studied for effectiveness, 17 were perceived as effective by the farmers, implying that many indigenous practices were both rational as well as effective. This calls for more scientific intervention to validate the indigenous knowledge, which in turn would enrich our agricultural technology.